Islam, Adat, and the State: Matrifocality in Aceh Revisited - Srimulyani, Eka (Al-Jamiah: Journal of Islamic Studies, 2010)
Matrifocality has been a rooted tradition in the social history of the community in Aceh. The principles of matrifocality have also affected on how women are positioned in the community, and the socio-gender relation within the community. The fact that Aceh has strongly associated to the Islamic values that claimed to support the paternal traditions. Apparently, the Islamic values and the local matrifocality practices juxtaposed through the roles of adat, which considered as inseparable to Islamic law or teaching, or in local term known as zat ngeun sifeut. Another point in revisiting matrifocality in Aceh in Aceh is an examination of how gender state ideology, particularly during the New Order Regime disregarded some local gender practices across some ethnics in the archipelago. Meanwhile, the state also hegemonied and promoted particular gender state ideology such as state ibuism. Nonetheless, the modernity and social changes have also contributed to the shifting of some matrifocality practices in contemporary Acehnese society. However, since the matrifocality has a strong root in the social life of the community, the principles of the matrifocality still survived until currently, although it transformed into ânew matrifocalityâ practices.